Phosphorylation of Not4p Functions Parallel to BUR2 to Regulate Resistance to Cellular Stresses in Saccharomyces cerevisiae - Lau, Nga-Chi (Public Library of Science, 2010)

(untitled)
BACKGROUND: The evolutionarily conserved Ccr4-Not and Bur1/2 kinase complexes are functionally related in Saccharomyces cerevisiae. In this study, we further explore the relationship between the subunits Not4p and Bur2p. METHODOLOGY/PRINCIPAL FINDINGS: First, we investigated the presence of post-translational modifications on the Ccr4-Not complex. Using mass spectrometry analyses we identified several SP/TP phosphorylation sites on its Not4p, Not1p and Caf1p subunits. Secondly, the influence of Not4p phosphorylation on global H3K4 tri-methylation status was examined by immunoblotting. This histone mark is severely diminished in the absence of Not4p or of Bur2p, but did not require the five identified Not4p phosphorylation sites. Thirdly, we found that Not4p phosphorylation is not affected by the kinase-defective bur1-23 mutant. Finally, phenotypic analyses of the Not4p phosphomutant (not4S/T5A) and bur2Δ strains showed overlapping sensitivities to drugs that abolish cellular stress responses. The double-mutant not4S/T5A and bur2Δ strain even revealed enhanced phenotypes, indicating that phosphorylation of Not4p and BUR2 are active in parallel pathways for drug tolerance. CONCLUSIONS: Not4p is a phospho-protein with five identified phosphorylation sites that are likely targets of a cyclin-dependent kinase(s) other than the Bur1/2p complex. Not4p phosphorylation on the five Not4 S/T sites is not required for global H3K4 tri-methylation. In contrast, Not4p phosphorylation is involved in tolerance to cellular stresses and acts in pathways parallel to BUR2 to affect stress responses in Saccharomyces cerevisiae.